Finance and Development, December 1988. (Finance and Development; Finance and Development ;, 1988)
This paper describes the effect of IMF-supported adjustment programs on the poor. The paper highlights that IMF-supported adjustment programs have often been misunderstood and have been criticized for seeking excessive reductions in aggregate demand, resulting in unwarranted contractions of output and employment opportunities, and declines in the living standards of people living in poverty. The paper discusses the series of case studies of nine programs in seven countries that the IMF undertook to obtain a balanced and comprehensive appraisal of how the poor fare in the context of IMF-supported adjustment programs.